Correlation between cholelithiasis and gallbladder carcinoma in surgical and autopsy specimens - Mlinarić-Vrbica, Sanja (Array, 2009)
Abstract: Gallbladder (GB) cancer is the most common malignant lesion of the biliary tract. The decision for a cholecystectomy in asymptomatic cholelithiasis as a measure of the secondary prevention of gallbladder cancer is based on the data of incidence and selected predictive factors for a specific population. A consecutive series of 3351 cholecystectomies in five year period was reviewed. That data was compared with the data from 2395 consecutive autopsies from the same period. Possible risk factors for gallbladder cancer were analysed. In surgical specimens, the incidence of gallbladder carcinoma was 0.62%. Of those, 24% were in patients younger than 60 years and 95.24% were associated with cholelithiasis. In autopsy material, in cases in which cholelithiasis was present, the incidence of gallbladder carcinoma was 3.4%. All cases were in patients older than 60 years and all were associated with cholelithiasis. Correlation between cholelithiasis and gallbladder carcinoma was most significant for women in the surgical group while it was not as strong for men or in the autopsy group. The results vary whether we analyse surgical or autopsy material, but in both cases female gender and the duration of cholelithiasis were significant risk factors. In our population GB cancer is not uncommon in elderly women with gall stones and is diagnosed in advanced stage if one waits for symptoms